2022
DOI: 10.1142/s0219519422400036
|View full text |Cite
|
Sign up to set email alerts
|

Development of Rail-Based Dynamic Rehabilitation Training System Considering User’s Movement

Abstract: Appropriate motion assistance based on understanding the patient’s exact intention plays an important role in improving the patient’s rehabilitation ability. This paper is a study on the development of user intention technology for a rehabilitation training system that performs dynamic rehabilitation training related to lower extremities such as posture balance and walking. The rehabilitation training system consists of a rail platform installed on the ceiling and a trolley with autonomous driving, weight supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The findings indicated that the use of gait assistive devices with ceiling-rails would allow effective gait training in daily life, as well as improve independence in daily activities. However, ceiling-rail gait assistive devices have so far only been developed to allow movement in fixed directions, and require a relatively large installation space [ 23 , 24 , 25 , 26 ]. Due to limited utility in daily life, these devices have previously mostly been installed in hospitals only.…”
Section: Introductionmentioning
confidence: 99%
“…The findings indicated that the use of gait assistive devices with ceiling-rails would allow effective gait training in daily life, as well as improve independence in daily activities. However, ceiling-rail gait assistive devices have so far only been developed to allow movement in fixed directions, and require a relatively large installation space [ 23 , 24 , 25 , 26 ]. Due to limited utility in daily life, these devices have previously mostly been installed in hospitals only.…”
Section: Introductionmentioning
confidence: 99%